2018
DOI: 10.20944/preprints201807.0495.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acute and Chronic Effects of Exercise on Appetite, Energy Intake and Appetite-Related Hormones: the Modulating Effect of Adiposity, Sex and Habitual Physical Activity

Abstract: Exercise facilitates weight control, partly through effects on appetite regulation. Single bouts of exercise induce a short-term energy deficit without stimulating compensatory effects on appetite, whilst limited evidence suggests that exercise training may modify subjective and homeostatic mediators of appetite in directions associated with enhanced meal-induced satiety.However, large variability in responses exists between individuals. This article reviews the evidence relating to how adiposity, sex and habi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 94 publications
(209 reference statements)
0
15
0
Order By: Relevance
“…Our data showed that these female professional Three of the athletes spent most of their training and competition days in sub-optimal EEA, with Athlete 4 performing up to 66% of her competition days in low EEA according to our estimations. Cyclists have been shown to be susceptible to low EA due to several reasons including practical difficulties of matching the energy expenditure during prolonged periods of cycling [18], while hunger may be suppressed for several hours following strenuous exercise [19]. The cyclists here reported particular difficulty in maintaining their dietary needs when traveling to foreign countries due to cultural differences in cuisine.…”
Section: Discussionmentioning
confidence: 87%
“…Our data showed that these female professional Three of the athletes spent most of their training and competition days in sub-optimal EEA, with Athlete 4 performing up to 66% of her competition days in low EEA according to our estimations. Cyclists have been shown to be susceptible to low EA due to several reasons including practical difficulties of matching the energy expenditure during prolonged periods of cycling [18], while hunger may be suppressed for several hours following strenuous exercise [19]. The cyclists here reported particular difficulty in maintaining their dietary needs when traveling to foreign countries due to cultural differences in cuisine.…”
Section: Discussionmentioning
confidence: 87%
“…GE was measured by adding 100 mg 13 C octanoic acid (Euriso-top) to the breakfast. Octanoic acid is a medium-chain fatty acid retained in food in the stomach but is rapidly absorbed in the duodenum and carried via the portal venous system to the liver where it is completely oxidised.…”
Section: Gastric Emptyingmentioning
confidence: 99%
“…Participants were provided with a breakfast that acted as a vehicle for the oils immediately after baseline measurements were taken. The breakfast consisted of porridge, semi-skimmed milk, honey, the added lipid and 13 At 4 h, participants were provided with a multi-choice ad libitum meal consisting of pasta with meat-free Bolognese sauce and cheese, white bread, cooked meats, sliced cheese, bananas, apples, oranges, chocolate biscuits and fruit juices.…”
Section: Test Breakfast and Ad Libitum Lunch Mealmentioning
confidence: 99%
See 2 more Smart Citations